P524 Gays, government and big data: should routine health records include sexual orientation?. (14th July 2019) - Saxton, Peter; Adams, Jeffery; Fenaughty, John; Exeter, Daniel; Sporle, Andrew
Abstract : Background: Sexual orientation minorities continue to experience poorer outcomes in sexual health, mental health and addictions. Despite clear information needs, routine data identifying gay, lesbian and bisexual (GLB) individuals are seldom collected by governments, rendering these populations invisible. In New Zealand (NZ), everyone is assigned a unique National Health Index (NHI) number used across all health systems to improve clinical and public health decision-making. In 2017 the NZ Ministry of Health proposed adding sexual orientation and other fields to NHI, however sexual orientation was rejected after consultation. We sought to better understand these viewpoints. Methods: We used the Official Information Act (OIA) to request the complete list of submitters, their support or opposition for adding sexual orientation and written comments. We allocated submitters to six groupings: Government (G); Health provider including District Health Boards (H); NGO or civil society (N); Academic (A); Data management firm (D) or Unspecified (U). Submitters did not necessarily represent the official views of their organisation. We present descriptive summaries and feedback themes. Results: 130 submissions were received. Overall 27 supported sexual orientation in NHI and 35 were opposed, the remainder being neutral or conditional. Support by grouping (high to low) was: Academic (100%); Government (56%); Unspecified (44%); NGO (40%); Health (36%) and Data firm (25%). Supportive reasons included: service planning; evidence-based policy; equity; GLB-specific health delivery (e.g. HPV vaccines, HIV and STI screening, pre-exposure prophylaxis); normalisation; health workforce development. Opposing reasons included: sexual orientation being irrelevant to clinical decision-making; classification challenges (e.g. sexual orientation fluidity); data quality; privacy; discrimination. Conclusion: Barriers to sexual orientation data collection include practical concerns but also well-meaning paternalism and heteronormative assumptions. Better information about NHI uses and protections, data governance, and healthcare service obligations to GLB communities, may improve support. Disclosure: No significant relationships.